Towards a Collaborative Governance Model for Preventing Child Marriage: Insights from Adaptive Co-management Literature - Sulfiani, Andi Ni'mah; Sangkala, ‎; Abdullah, Muhammad Tang; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
Child marriage is a complex social issue that requires a collaborative governance approach involving multiple sectors and stakeholders. Sectoral interventions have proven insufficient in addressing the root causes of early marriage, particularly in regions with strong socio-cultural characteristics. Adaptive Co-Management, as developed by Armitage, Berkes, and Doubleday, offers an adaptive, participatory, and socially-driven governance framework. This article aims to systematically review the literature on adaptive co-management in the context of multi-stakeholder collaboration and to explore its relevance to child marriage prevention efforts. Utilizing a systematic literature review (SLR) approach guided by the PRISMA protocol, this study identifies and analyzes 43 relevant scholarly articles from the Scopus, Web of Science, and ScienceDirect databases. The main findings indicate that key elements such as local actor engagement, social learning mechanisms, and institutional flexibility are crucial for establishing effective collaborative governance. This article proposes an initial conceptual framework for an adaptive collaborative governance model that can serve as a foundation for policy formulation and child marriage prevention interventions at the local level.